Développer la culture du paysage chez les acteurs locaux : la démarche du Parc naturel régional de la Narbonnaise en Méditerranée à l’épreuve de la pression urbaine - Pierre Dérioz; Philippe Béringuier; Maud Loireau (Développement Durable et Territoires)
The article analyses urban projects and governance of urban planning in a fast growingurban community (Grand Narbonne, Aude, France), focusing on the approach of the local stakeholders, between interest and distrust, about landscape considered as a dimension of the urban project and as a tool for collective thinking about urban planning. Trying to overcome what appears to be a sort of consensus about the importance of the landscape dimension due to the European Landscape Convention and to the evolution of the French legislative framework, the paper tries to highlight the processes of emergence and diffusion of a collective “culture of landscape” applied to urban planning. The part played in these processes by the regional natural park of the “Narbonnaise en Mediterranée” is thoroughly analysed, as well as the limits of its actions. The study also takes into account the strengthening of the intercommunal institutions, which broadens the local system of governance.